Quantification of performance, damage, and risk to light wood frame buildings subjected to tornadoes and expansive soils - Maloney, Timothy D., author; Mahmoud, Hussam N., advisor; Ellingwood, Bruce R., advisor; van de Lindt, John W., committee member; Zahran, Sammy, committee member (Colorado State University. Libraries, 2017)
Each year, damage to infrastructure caused by the uncorrelated hazards of tornadoes and expansive soils is on the order of billions of dollars. The monetary losses caused by each hazard alone are reason for concern. For tornados, however, the impact can be devastating and extend beyond monetary loss. Furthermore, the presence of expansive soils can exacerbate life-safety concerns during a tornado by limiting construction of underground shelters such as basements. It is not uncommon for communities to be crippled by damage to critical infrastructure such as businesses, homes, utility networks, and emergency facilities. This destruction can limit a community's ability to support its population in the short-term which can lead to significant outmigration that may be difficulty to recover from. The ability of a community to plan for and recover from such hazards is referred to as community resilience. The major goal of this research is to contribute to the development of a set of standards and guidelines for resilient community design. Specifically, this study aims to link the performance of individual building components to building system performance, so that the effect of implementing a change in standard construction techniques (i.e. recommending that homes be constructed with hurricane clips) can be quantified. The work herein focuses on light wood frame residential buildings constructed with methods typical in the American heartland. The research approach taken herein was to develop detailed finite element (FE) models to capture building system performance and individual building component behavior under expansive soil and tornado loading. The level of detail used in the FE models allows the interaction between building components to be captured to a higher degree than previously possible. Knowledge of the demand on building components gained from the FE analysis was then applied to perform statistical analysis to quantify the performance of several building archetypes chosen to represent the residential building portfolio in a typical community located in the US heartland. The performance of the typical archetypes was then analyzed to identify deficient building components and compared to target resilience performance levels provided by research partners at the University of Oklahoma. The effect of implementing various improved construction techniques was then examined in an effort to meet the resilience performance targets. This study revealed that, typically, light wood frame residential construction that is common in tornado prone areas of the U.S. is not sufficient to meet the resiliency goals considered in this study. This is unsurprising considering the historical lack of consideration given to tornado hazards in U.S. design codes and standards. Similarly, it was found that typical masonry block basement wall construction was insufficient to withstand loading from expansive soils without sustaining damage. This is also not surprising because many people in expansive soil prone areas choose to forgo constructing basements due to the likelihood of damage. The study also revealed, however, that resilience target performance levels can be achieved using existing construction techniques. This suggests that resilient community design is a goal that is already within reach at the current state of the art.
Keywords: expansive soils; light wood frame; community resilience; tornado; finite element modeling